2019
DOI: 10.1248/bpb.b19-00357
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Optimal Dose of Irinotecan for Patients with Heterozygous Uridine Diphosphate-Glucuronosyltransferase 1A1 (<i>UGT1A1</i>)

Abstract: Uridine 5′-diphospho-glucuronosyltransferase (UGT), a metabolic enzyme of irinotecan active metabolite, has two genetic polymorphisms (UGT1A1*6 and UGT1A1*28). In UGT1A1 homozygous or heterozygous patients, metabolism is delayed and the risk of developing adverse effects is increased, and therefore, dose reduction of irinotecan is considered. However, the specific dose reduction rate of irinotecan for heterozygous patients is uncertain. We studied the necessity of irinotecan dose reduction and its optimal dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The association of UGT1A1*6 polymorphisms with severe diarrhea was evident in only patients with colorectal cancer but not in patients with lung cancer who received a lower irinotecan dose than the former. Konaka et al, based on a Japanese study (n = 31), suggested that among patients with UGT1A1 polymorphisms, a dose reduction of approximately 20% could lead to chemotherapy administration with lesser AEs but similar efficacy [25].…”
Section: Discussionmentioning
confidence: 99%
“…The association of UGT1A1*6 polymorphisms with severe diarrhea was evident in only patients with colorectal cancer but not in patients with lung cancer who received a lower irinotecan dose than the former. Konaka et al, based on a Japanese study (n = 31), suggested that among patients with UGT1A1 polymorphisms, a dose reduction of approximately 20% could lead to chemotherapy administration with lesser AEs but similar efficacy [25].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, consideration for testing should be given to DPYD for fluoropyrimidines, 20 TPMT and NUDT15 for thiopurines, 21 and UGT1A1 for irinotecan. 22 Additional situations in which pharmacogenomic tests may be particularly useful are unexplained sensitivities or toxicities with multiple drugs not otherwise explained by drug interactions. 23 Sometimes metabolic patterns can be initially detected by considering the metabolism of drugs and the problems (eg, efficacy/adverse effects) that the patient has had in the past.…”
Section: Article Highlightsmentioning
confidence: 99%
“…60,62 Of note, several genes that are commonly tested for pharmacogenomic purposes are also associated with disease states. For example, G6PD genetic variants have implications for many drugs, and variants in this gene are known to cause glucose-6phosphate dehydrogenase deficiency, 63 and UGT1A1 variation affects irinotecan 22 and atazanvir 64 but also can result in Gilbert syndrome or Criger-Najjar syndrome. 65 For these and other genes associated with hereditary disorders, it is important for providers to be aware of the possibility of a secondary finding in addition to gaining information about drug metabolism so that the patient is appropriately counseled before testing.…”
Section: What Are Some Of the Additional Clinical Considerations?mentioning
confidence: 99%
“…The use of pharmacogenetic testing in the clinical setting is still limited to a few drugs, but genetic testing is covered by insurance in the USA, Japan, and some other countries 7,10,11 . In Japan, only the aforementioned 2 genetic tests ( UGT1A1 and NUDT15 ) are covered by insurance to avoid or predict the likelihood of the patient developing severe ADRs in response to cancer treatment.…”
Section: Introductionmentioning
confidence: 99%